Founder’s Added Value in a Startup Valuation. Could an Expert be Worth an Extra Penny? - Cheng, Yan de Arruda; Roquete, Raphael Moses; Campani, Carlos Heitor (Revista Ciências Administrativas, 2021)
The Brazilian Startup market has been growing fast recently, but the assessment of a startup company is still considered a black box by many authors and investors in the market. The main reason for the difficulty of evaluating a startup is the lack of a universal methodology applicable to this type of company. In this article, the authors tested an alternative way to evaluate a company using key variables from the founder’s experience. Approximately 30 Brazilian VC funds and the profile of 130 founders with public data were analyzed, and we found significance in the founder’s senior management experience before the funding stage. The result is still basic to consider a new assessment approach for startups, but the main conclusion of this article is relevant: the experience of senior management has a significant and consistent impact on the assessment of a startup in Brazil.